Does acupuncture combined with antidepressants have a better therapeutic effect on post-stroke depression? A systematic review and meta-analysis. Issue 5 (October 2021) - Zhang, Kun; Cui, Guangwei; Gao, Yuan; Shen, Weidong
Objective: To evaluate the effectiveness of acupuncture combined with antidepressants in the treatment of post-stroke depression (PSD). Methods: The following electronic databases were systematically searched: PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, Wanfang Data, China National Knowledge Infrastructure and Chongqing VIP database. The primary outcome was the Hamilton depression scale (HAMD) score. Two independent investigators screened for eligible clinical trials. The Cochrane risk of bias tool was used to assess the methodological quality, and RevMan 5.3 was applied for meta-analysis. Results: Thirteen randomized controlled trials (RCTs) involving 904 participants were included in the study. The results of this meta-analysis showed that, compared with antidepressants alone, acupuncture combined with antidepressants led to a significant decrease in the HAMD score (mean difference (MD): −3.60, 95% confidence interval (CI): −4.25 to −2.95, P < 0.001), had a better effective rate (risk ratio (RR): 1.33, 95% CI 1.19 to 1.49, P < 0.001) and lower National Institutes of Health Stroke Scale (NIHSS) scores (MD: −2.39, 95% CI: −3.37 to −1.41, P < 0.001), and led to a significant increase in the Barthel index scores (MD: 8.10, 95% CI: 5.25 to 10.94; P < 0.001). Conclusions: Acupuncture combined with antidepressants showed a more favourable effect on the treatment of PSD than antidepressants alone. However, given the limited methodological quality, more high-quality RCTs conducted based on the Consolidated Standards of Reporting Trials (CONSORT) and Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) guidelines are necessary.